Polaron relaxation in a quantum dot due to anharmonic coupling within a mean-field approach - Stauber, Tobias Pascal (2009)
We study the electronic relaxation in a quantum dot within the polaron approach by focusing on the reversible anharmonic decay of longitudinal optical LO phonons forming the polaron into longitudinalacoustic LA phonons. The coherent coupling between the LO and LA phonons is treated within a mean-field approach.We derive a temperature-dependent interlevel coupling parameter, related to the Grüneisen parameter and the thermal-expansion coefficient, which characterizes an effective decay channel for the electronic or excitonic states. Within this theory, we obtain a characteristic anharmonic decay time of 1 ns, 2–3 orders of magnitude longer than previous predictions based on the Fermi’s Golden Rule. We suggest that coherent relaxation due to carrier-carrier interaction is an efficient alternative to the (too slow) polaron decay.